Domestic Wastewater Contribution to Water Quality of Brantas River at Dinoyo Urban Village, Malang City - Sonia Prilly Ismi Arum; Donny Harisuseno; Soemarno Soemarno (Graduate Program, 2019)
Domestic wastewater from human activities in densely populated settlements could affect the quality of streamflow because its organic matter could affect the amount of oxygen in aquatic ecosystems as an impact from biological and chemical degradation processes. The main aim of this research was to analyze the contribution of domestic wastewater from Dinoyo Urban Village settlement to the water quality of Brantas River on BOD and COD concentrations. The sampling of water and respondents were taken by purposive sampling method. The water sampling using grab sample method was performed at upstream, middle, and downstream stations of the river segment. The Estimation Method by regulation was employed to calculate BOD and COD emissions. The results showed that BOD concentrations were between 12.7 to 13.627 mgl-1 and COD concentrations were between 26.677 to 28.197 mgl-1. The amount of BOD emission was 539 kg/day and COD emission was 1032 kg/day which were dominated by human activities in bathing, washing, and lavatory. It concluded that domestic wastewater from settlement contributed to the streamflow quality by the increase on BOD and COD concentrations at each sampling points and it could not be used to its utility because it exceeded the class II of water quality standards.